Ion rarefaction waves and associated phenomena - Coates, A (1982)
﻿ This thesis contains an experimental and theoretical study of the response of a plasma to the motion of the positive space-charge sheath which bounds it. It is known theoretically that, if a sheath edge is moved at a speed less than the speed of ion acoustic waves, a region of ion rarefaction propagates into the plasma at the ion acoustic speed. In the past, difficulty has been encountered with the theory of ion acoustic wave generation from moving sheath edges, where compressions are necessary in addition to rarefactions. The initial conditions of many previous calculations omit the formation of a steady-state presheath where ions are accelerated to form the sheath. Some calculations are described which include the effects of an initial presheath by constructing a one-dimensional plasma solution where a production term balances the losses of ions to the walls. The plasma response to the motion of one boundary is found using the method of characteristics with appropriate boundary conditions. Ion rarefaction waves are associated with expanding sheaths while ion 'enhancement' waves (compressive features) are formed on sheath collapse. In each case the wave front moves at the local ion acoustic speed which includes the effects of ion drift. The presence of the presheath is essential to the generation of enhancements. The constructional details of a multidipole device are discussed, and the results of Langmuir probe and ion acoustic wave experiments are used to determine the parameters of a quiescent argon plasma. Some experiments on moving sheaths in such a plasma are then considered. Negative voltage ramps are applied to a plate and the plasma response is measured using sampled probe techniques. As the plate-plasma voltage increases, the ion-rich sheath expands at a speed which depends on the applied voltage waveform. For sheath edge speeds less than the ion acoustic speed, an ion rarefaction wave is formed. As the voltage decreases, the sheath collapses and an ion enhancement wave propagates into the plasma. Both wavefronts are observed to move at the local ion acoustic speed which increases with distance from the plate in agreement with theory.